2017
DOI: 10.1016/j.ajhg.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Multi-ethnic Evidence for Risk Assessment of Quantitative Traits in Minority Populations

Abstract: An essential component of precision medicine is the ability to predict an individual's risk of disease based on genetic and non-genetic factors. For complex traits and diseases, assessing the risk due to genetic factors is challenging because it requires knowledge of both the identity of variants that influence the trait and their corresponding allelic effects. Although the set of risk variants and their allelic effects may vary between populations, a large proportion of these variants were identified based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…This is in agreement with the work of Coram, Fang, Candille, Assimes, and Tang (2017), who assumed different effect sizes between populations and found that estimating effect for risk prediction purposes is useful in ethnically matched population, whereas SNP selection using EA GWAS is generally appropriate. Based on simulation results, if the causal SNPs are the same and have the same effect sizes in all EA and Hispanic/Latino populations, we would expect that EA-based SNP selection combined with either EA or META weights would have optimal performance.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the work of Coram, Fang, Candille, Assimes, and Tang (2017), who assumed different effect sizes between populations and found that estimating effect for risk prediction purposes is useful in ethnically matched population, whereas SNP selection using EA GWAS is generally appropriate. Based on simulation results, if the causal SNPs are the same and have the same effect sizes in all EA and Hispanic/Latino populations, we would expect that EA-based SNP selection combined with either EA or META weights would have optimal performance.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, transancestry studies have been increasingly popular. They incorporate genotype data from different ancestries to boost statistic power with increasing sample sizes, which have the benefit to discover disease/trait-associated loci and fine-mapping causal variants associated with complex traits or diseases 13,[40][41][42][43] . However, the structure of the reference population still remains to be thoroughly explored, such as whether some specific populations with certain sample sizes are mostly useful in trans-ancestry studies.…”
Section: Discussionmentioning
confidence: 99%
“…Key methodological considerations for GWAS in ancestrally diverse populations have been recently discussed, including the choice between performing a meta-analysis stratified by ethnic groups and performing a joint mixed-model across all participants [23]. Novel methods for 'polyethnic' scores, like XP-BLUP and Multi-ethnic PRS, which improve predictive accuracy by combining transethnic with ethnicspecific information, are being developed [30][31][32].…”
Section: Applicability Of Prs Across Ethnic Groupsmentioning
confidence: 99%